2019
DOI: 10.1186/s13068-019-1450-7
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing of a BAHD acyltransferase in sugarcane increases biomass digestibility

Abstract: Background Sugarcane ( Saccharum spp.) covers vast areas of land (around 25 million ha worldwide), and its processing is already linked into infrastructure for producing bioethanol in many countries. This makes it an ideal candidate for improving composition of its residues (mostly cell walls), making them more suitable for cellulosic ethanol production. In this paper, we report an approach to improving saccharification of sugarcane straw by RNAi silencing of the recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…Recent studies highlight that lowering p CA and FA in grass cell walls leads to a decrease in biomass recalcitrance and thereby an increase in biomass digestibility (Li et al ., 2018; de Souza et al ., 2019). Thus, decreasing p CA or FA contents of grass biomass is a promising strategy for increasing digestibility for biofuel production or animal feeding (Oliveira et al ., 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies highlight that lowering p CA and FA in grass cell walls leads to a decrease in biomass recalcitrance and thereby an increase in biomass digestibility (Li et al ., 2018; de Souza et al ., 2019). Thus, decreasing p CA or FA contents of grass biomass is a promising strategy for increasing digestibility for biofuel production or animal feeding (Oliveira et al ., 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that SvBAHD01 is a feruloyl transferase responsible for the addition of FA onto Ara f residues linked to AXs. Furthermore, we recently showed that silencing of SvBAHD01 ortholog in sugarcane ( SacBAHD01 ) led to similar results to those demonstrated in S. viridis (de Souza et al ., 2019). We were interested in characterizing the other BAHD gene in S. viridis and, for that, we selected SvBAHD05 , the ortholog of BdAT1 that appears to act in the addition of FA to AX in Brachypodium distachyon (Buanafina et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The BAHD superfamily has members in various ester synthetic pathways. The functions of several BAHD genes have been reported [43][44][45]. Here, by detecting their HXXXD and DFGWG motifs using a HMMER search, we identified 717 BAHD genes from seven Rosaceae species.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of BdBAHD05 (also called BdAT1) caused a moderate increase in FA content and downregulation showed a moderate decrease (Buanafina et al, 2016;de Souza et al, 2018). Analysis in sugarcane revealed six BAHD genes, one of which is homologous to SvBAHD01, and downregulation of SacBAHD01 similarly reduced stem FA content and increased biomass digestibility (de Souza et al, 2019).…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 99%